Re-resection of remnant Caroli syndrome six years after the first resection (case report). (2016) - Zidan, Ahmed; Bauschke, Astride; Scheuerlein, Hubert; Settmacher, Utz; Rauchfuss, Falk
Highlights: Caroli syndrome is characterized as multiple dilatation of intrahepatic bile ducts and congenital hepatic fibrosis. We presented a case with previous history of liver resection due to Caroli syndrome. Inadequate resection leads to re-enlargement of the remnant and recurrence of biliary symptoms. Use of intraoperative imaging is advisable to ensure appropriate resection of Caroli disease. Abstract: Introduction: Caroli syndrome is characterized as multiple cystic or saccular dilatations of intrahepatic bile ducts (Caroli disease) and congenital hepatic fibrosis. Diagnosis depends on histological features and imaging, which shows communications between the sacculi and bile ducts. Presentation of a case: In our case, the patient had segments II/III liver resection six years ago for Caroli syndrome. A follow-up CT after four months of the operation revealed remnant cysts in segment IV, which needed another surgical intervention to resect the remnant cysts and segment IV after six years from the first operation. Disscussion: In our case, we were surprised that patient has remnant of the primary benign disease in the follow-up CT after only four months of the previous operation. This remnant continued to increase in size with recurrent attacks of cholangitis until liver abscess developed and required another surgical intervention. Conclusion: Imaging is essential in planning the operative treatment to detect the extent of the Caroli disease and define the extent of resection. Any residual disease due to inappropriate imaging planning may cost the patient another cycle of suffering and may need another surgical intervention as in our case. We recommend using intraoperative ultrasound for accurate determination of the line of resection.